Property evolution of geopolymer composites with SiC whiskers loaded with BN coating at elevated temperatures. (22nd November 2021) - Fang, Yuan; Wang, Aoxuan; He, Keze; Pan, Hongying; Liao, Jiajun; Ding, Zhu; Xing, Feng; Le, Huirong; Wang, Xianfeng
Highlights: The crucial interfacial bonding mechanism of geopolymer composites was explored. SiCw modified by BN can improve the polymerization degree of geopolymer matrix. BN/SiCw optimizes the composites at high temperatures by improving pore structures. The BN coating can optimize the pull-out effect and improve fracture mode. Abstract: This article investigates the key interface properties of geopolymers reinforced by SiC whiskers loaded with BN coating (BN/SiCw) and the insight of mechanical performance and microstructures of the resulting composites. The interesting diverse strength evolutions of geopolymer composites calcinated at various temperatures suggest a result of rivalries of multiple factors including BN coating, geopolymer matrix transformations, SiC whiskers. A positive effect on whisker pull-out phenomenon has been achieved via the chemical bonding between SiC whisker (SiCw) and BN coating and the rough physical interface between BN coating and geopolymers; the addition of SiCw and BN/SiCw promotes the polycondensation reaction of geopolymers and the addition of the latter is superior. Through changing the pore structure characteristics of the composites, the SiCw in composites can release their excessive vapor pressure in the closed pores which is the main reason attributing to the strength loss of geopolymers at 900 °C. In addition, BN coating can make up for the mismatch of thermal expansion coefficient between SiCw and geopolymers, increasing the strength of the composites by 30.9% at 900 °C, whereas whisker pull-out and crack deflection are the main toughening effect for BN/SiCw.